2007
DOI: 10.1002/ar.20519
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anatomy of brachial plexus branches in Wistar rats

Abstract: In the present study, we analyze the morphology and morphometry of the lateral proper digital nerve of the third finger, and of the proximal and distal segments of the ulnar, median, and radial nerves, in Wistar rats 4 or 7 weeks old. The fascicular area and diameter were generally significantly greater in the proximal compared to distal segments and tended to be larger in 7-week-old compared to 4-week-old rats (e.g., median nerve area of 0.13 mm 2 for the proximal and 0.07 mm 2 for distal segments in 4-weekol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
5
33
0
1
Order By: Relevance
“…The absence of significant branching of the sciatic nerve (Schmalbruch) associated with a constant number of nerve fibers during development (Jeronimo et al) explains our findings. Also, the absence of significant difference in the number of fibers between proximal and distal segments in animals of the same age has been documented for the sciatic and other nerves (Dyck et al, 1984;Jeronimo et al;Santos et al). The numbers presented in this section are similar to those reported for Wistar rats (Schmalbruch; Yagihashi et al; Voinesco et al; Prodanov & Feirabend); and for Lewis and Sprague-Dawley rats (Dyck et al;Mackinnon et al, 1991).…”
Section: Minimal Fascicular Area and Diameter And Capillariessupporting
confidence: 80%
See 1 more Smart Citation
“…The absence of significant branching of the sciatic nerve (Schmalbruch) associated with a constant number of nerve fibers during development (Jeronimo et al) explains our findings. Also, the absence of significant difference in the number of fibers between proximal and distal segments in animals of the same age has been documented for the sciatic and other nerves (Dyck et al, 1984;Jeronimo et al;Santos et al). The numbers presented in this section are similar to those reported for Wistar rats (Schmalbruch; Yagihashi et al; Voinesco et al; Prodanov & Feirabend); and for Lewis and Sprague-Dawley rats (Dyck et al;Mackinnon et al, 1991).…”
Section: Minimal Fascicular Area and Diameter And Capillariessupporting
confidence: 80%
“…They were then prepared, cut, stained, and observed as described previously (Santos et al, 2007). The nerves were kept in the fixative solution for an additional 48 h and processed for epoxy resin embedding (Poly/Bed 812; Polysciences, Warrington, PA).…”
Section: Methodsmentioning
confidence: 99%
“…The nerve was cut into 0.5 μm thick sections using a microtome (MT 6000XL-RMC), stained with toluidine blue, and mounted using Entellan ® for light microscopy analysis. Details of the methods used have been published in previous studies 6,20,21 .…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The brachial plexus of rat is formed by contribution of ventral rami of C5, C6, C7, C8, T1 and T2 spinal nerves (Santos et al 2007). On the other hand, in literature it is reported that ramus ventralis of T2 spinal nerve in rats is not involved (Bertelli et al 1992).…”
Section: Discussionmentioning
confidence: 99%